The Government Should Invested in Child as Child Support Grant : Social Protection of Child in Thailand - จิรวัฒนานนท์ มาลี (Journal of Social Work and Social Administration, 2019)
In cooperation between Thai Government and The United Partnership Framework (UNPAF) from the year 2012 to 2016, children were one of the targets within the Social Protection Floor (SPF). So this article would like to show that the Convention on the Rights of the Child(CRC) should be promoted by the government. The government should released social policy like Child Support Grant(CSG) to support the families who cared their children. At the presents, families faced many social change situations those made them vulnerability and less capacity to look after their children. To be supported, several types and economic classes families were available to things and accessed social services for look after their children in better quality lives. Moreover, the demography data illustrated that the number of child population decreased continuously, in the other hand the number of aging population were increasing. In 2012, the number of child population was 13.2 million and aging population was 7.5 million. Approximately 20 years later, in 2030, demographer forecasted that the amount of child population would be 9.8 million and aging population would be 14.6 million. In Thai society, the child birth rate was lower than the past that would impacted how young generation cared aging in their families and the aging society. The Government should invested in child as Child Support Grant(CSG) for social investment because the rights of the child to be survival, participation, protection and development was public issues. Child Support Grant(CSG) provided better chance to children and their families to access the need and many social services. The golden period of children’ development was childhood or pre-school children so the quality life of children, especially in the important period of human development, would effected to quality life of people and their potential for developing themselves and their country. Social Protection Floor(SPF) as Child Support Grant(CSG) would be the social welfare that increased alternative chances for different types of families to raised their children less hardship and that would enhanced not only the Convention on the Rights of the Child(CRC), but social justice also.